Effect of Immersion Media on the Swelling Degree of Banana Peel Extract-Based Biofilm - Muthia Muthmainnah Ismail; Mira Setiana (Jurnal Pijar MIPA, 2026)
The waste from banana peels has bioactive chemicals that could be exploited as natural biomaterials for wound dressings. The amount of swelling in a biofilm is one of the most crucial things that impacts how effectively it works for wound care. This is because it changes how much water it can hold and how solid its structure is. The purpose of this study is to determine the impact of immersion media on the swelling of banana peel extract-based biofilms. We mixed banana peel extract with gelatin at 0.1, 0.3, and 0.5 mL to form biofilms. We tested for swelling in distilled water and a 0.9% NaCl solution for 10 to 30 minutes. We calculated out how much the swelling changed by comparing the weights before and after immersion. After that, we looked at the data by finding the average swelling numbers. The findings indicated that biofilms immersed in NaCl solution exhibited greater swelling than those immersed in pure water. This means that ionic interactions affect how polymer networks grow. The biofilm with 0.3 mL of extract swelled the most, although greater concentrations of extract made the swelling more controllable. These findings indicate that the concentration of the extract and the nature of the immersion medium significantly influence the swelling behavior of banana peel extract-based biofilms. This work provides scientists with insights into enhancing natural biofilm compositions for use as stable and absorbent, eco-friendly wound dressings.